Role of Soil Management in Control of Soil-Borne Diseases - Gretchen F. Sassenrath; Christopher R. Little; Xiaomao Lin (Kansas Agricultural Experiment Station Research Reports, 2024)
Soil-borne diseases are a significant cause of crop yield reduction. Alternative soilmanagement methods can enhance the soil’s natural disease-controlling organisms. This study explores the effect of alternative production methods on a primary soybean disease, charcoal rot, caused by the fungus Macrophomina phaseolina. Treatments that could potentially enhance or reduce the disease pressure were implemented, and soil tests were conducted for nutrients, soil properties, and disease presence. Manure increased the nutrient levels in the soil, as expected, but did not influence disease control. Solarization increased the temperature within the plots and increased the number of colony-forming units (CFUs) of M. phaseolina.
Keywords: charcoal rot; soil-borne disease; soybeans